Quantum Magnetic Imaging of Iron Biomineralization in Teeth of the Chiton Acanthopleura hirtosa. Issue 3 (19th January 2020) - McCoey, Julia M.; Matsuoka, Mirai; de Gille, Robert W.; Hall, Liam T.; Shaw, Jeremy A.; Tetienne, Jean‐Philippe; Kisailus, David; Hollenberg, Lloyd C. L.; Simpson, David A.
Abstract: Iron is critical for life. Nature capitalizes on the physical attributes of iron biominerals for functional, structural, and sensory applications. Iron biomineralization is well exemplified by the magnetite‐bearing radula of chitons, the hardest known biomineral of any animal. Although magnetism is an integral property of iron biominerals, limited information exists on the magnetic state, structure, and orientation of these nanoscale materials during mineralization. The advent of quantum‐based magnetic microscopy provides a new avenue to probe these biological systems directly, providing detailed magnetic information of the iron oxide structures. Here two complementary quantum magnetic microscopy methods are applied, based on nitrogen‐vacancy centers in diamond, to spatially map the mineral phases ferrihydrite and magnetite in the developing teeth of the chiton Acanthopleura hirtosa . The images reveal previously undiscovered long‐range magnetic order, established at the onset of magnetite mineralization. This is in contrast to electron microscopy studies that show no strong common crystallographic orientation. The implications of these results are important, not just for the insights gained in biomineralization of the target organism, but also for the study of a broad range of iron minerals in the physical and biological sciences. Abstract : A quantum‐based magnetic imaging technique for characterizing iron biominerals is reported. Chitons—marine molluscs—are an ideal model of the poorly understood process of iron biomineralization. By applying diamond magnetic microscopy, the key components of chiton teeth, namely magnetite, and its precursor, ferrihydrite, are mapped with submicron resolution. Significantly, long‐range magnetic order at early stages of tooth development is revealed.